Genetic Diversity and Agromorphological Characteristics of 50 Upland Rice Genotypes Derived from Recurrent Selection - Yono, Sahri; Herawati, Reny; Pujiwati, Hesti (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2018)
Rice (Oryza sativa L.) is the most important crops commodity in Indonesia because it is the main staple for the people of Indonesia but currently, in Indonesia, the production of rice is still not maximal so it can not meet the demand of Indonesian people for national food needs. Therefore, it is necessary for rice plants that have high production and tolerant to various stresses. Plant breeding is one of the ways that can be done to increase the production of rice, one of which is the method of cross-recurring selection. Genetic diversity is a variation of characteristics that are inherited in the same species population. This study aims to obtain information about genetic diversity and agro-morphological characters of 50 genotypes rice derived from the recurrent selection. This research was conducted from August until December 2017 in Rawa Makmur Village, Bengkulu Province with the height of place from sea level ± 2 m. The study used a Completely Randomized Block Design (RAK) with 3 replications. The seeds used were 50 genotypes of rice from previous cross-selection results from Bugis/N-22 crossbreeds, Bugis/IR-7858-1, Sriwijaya/N-148, Sriwijaya/IR-7858-1. The results showed that the genetic diversity of rice is quite narrow to moderate, but there are some rice characters that have medium to high heritability value that was plant height, harvesting age, flowering age, the total number of tillers and panicle length, so that character can be used for the next generation rice selection. The genotypes produced by Bugis/IR-7858-1 crosses have panicle length, filled grain per panicle, and high grain weight/hill resulting in high yield potential.